Factors affecting confidence and knowledge in spinal palpation among International Manual Physical Therapists. (26th May 2016) - Karas, Steve; Schneiders, Anthony; Reid, Duncan; Talisa, Victor
Abstract : Objectives : We sought to find if there was a relationship between the confidence in use of static palpation, passive physiological intervertebral motion (PPIVM) and passive accessory intervertebral motion (PAIVM) and the manual therapist's (MTs) knowledge of the literature on these topics. Methods : We designed an international survey to achieve our objectives. Each skill was surveyed for the cervical, thoracic and lumbar spines. We also included several other factors that we believed might influence the use of these skills. Results : We concluded that familiarity of the literature was significantly associated with a MTs' confidence in the use of static palpation, PPIVM and PAIVM techniques. We also found a relationship with the country of practice of the MT and their confidence using these techniques. Discussion : Spinal palpation is an integral part of the MT's evaluation and treatment abilities. The vast majority of MTs use spinal palpation and nearly all entry-level education programmes include it in their training. Knowing what factors influence MTs' confidence assessing and treating the spine may allow for more effective teaching and training, as well as improved patient outcomes.